พฤติกรรมส่งเสริมสุขภาพและภาวะสุขภาพของผู้สูงอายุที่มีภาวะสมองเสื่อมในระยะแรก - กรรณิกา ปิงแก้ว (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Dementia is a significant public health problem among the elderly. In the early stages of dementia, older persons may notice some memory loss but they are still able to perform activities of daily life. The incidence of dementia will increase if there are no prevention programs to delay the severity of dementia. Health promoting behaviors is an appropriate way to address risk factors and reduce severity of the disease. The purpose of this descriptive study was to investigate health promoting behaviors and health status among older persons and to examine the relationship between health promoting behaviors and health status. The conceptual framework for this study was the Pender’s Health Promotion Model (Pender et al., 2006) and related literatures. One hundred and six older persons with early stage dementia who attended at outpatient department of Chiangmai Neurological Hospital were chosen as study subjects. The instruments used for data collection were a demographic data recording form, health promoting behaviors among older persons with dementia questionnaire developed by the researcher and an advisory committee, and health status among older persons with dementia questionnaire was modified from that of Paijitra Loskultong based on literature reviewed by the researcher and the advisory committee. The content validity of the questionnaires were tested and approved with a content validity index values of 0.82 and 1.00 respectively. Reliability was assessed by Cronbach’s alpha coefficient and were 0.84 and 0.88 respectively. Descriptive statistics and Pearson’s product moment correlation coefficient were used for data analysis. The results of the study revealed that: 1. Overall health promoting behaviors were at a high level (53.70%) with an average score of 47.39 (S.D.=4.52). Physical activity was at a low level (39.60%) with an average score of 7.59 (S.D.=2.08). Nutrition was at high level (96.30%) with an average score 26.46 (S.D.=1.83). Personal relations was at a moderate level (67%) with an average score of 13.34 (S.D.=2.21). Health status was at a moderate level (61.30%) with an average score of 79.63 (S.D. = 8.59). 2. There were a statistically significant positive correlation among health promoting behaviors and health status (r=.204, p<.05). There was a statistically significant positive correlation between personal relation and health status (r=.303, p<.01), while physical activity and nutrition were not correlated with health status. The results of this study can be used as baseline information for health personnel when planning to promote appropriate health promoting behaviors for older persons with early stage dementia.